2011
DOI: 10.1016/j.jenvrad.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Arrival time and magnitude of airborne fission products from the Fukushima, Japan, reactor incident as measured in Seattle, WA, USA

Abstract: We report results of air monitoring started due to the recent natural catastrophe on 11 March 2011 in Japan and the severe ensuing damage to the Fukushima Dai-ichi nuclear reactor complex. On 17-18 March 2011, we registered the first arrival of the airborne fission products 131 I, 132 I, 132 Te, 134 Cs, and 137 Cs in Seattle, WA, USA, by identifying their characteristic gamma rays using a germanium detector. We measured the evolution of the activities over a period of 23 days at the end of which the activities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 12 publications
7
36
1
1
Order By: Relevance
“…Progressive decline of 131 I in precipitation at our location was faster than can be attributed to radioactive decay, indicating efficient washout of iodine from the atmosphere by abundant spring rain (70 mm March 11 -April 11, and 120 mm April 11-May 11). A similar effect was observed for Chernobyl fallout (17).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Progressive decline of 131 I in precipitation at our location was faster than can be attributed to radioactive decay, indicating efficient washout of iodine from the atmosphere by abundant spring rain (70 mm March 11 -April 11, and 120 mm April 11-May 11). A similar effect was observed for Chernobyl fallout (17).…”
Section: Resultssupporting
confidence: 81%
“…Given that the cosmogenic production of 7 Be in the atmosphere is approximately constant (15), we attribute the second 131 I peak to more efficient removal of radionuclides from the atmosphere rather than to a secondary pulse of 131 I from Japan. In this manner, the 131 I∶ 7 Be ratio (Table S1) at our location provides a metric that is consistent with the history of the FDNPP plume approaching North America (17). Progressive decline of 131 I in precipitation at our location was faster than can be attributed to radioactive decay, indicating efficient washout of iodine from the atmosphere by abundant spring rain (70 mm March 11 -April 11, and 120 mm April 11-May 11).…”
Section: Resultssupporting
confidence: 77%
“…The clean association of Tokyo 23 waste reports that ashes contain radioactive substance continuously after the disaster. In addition, burning earthquake debris derived from the northeast regions in Japan is another significant concern of spreading radioactive particles because burning earthquake debris could make secondary spreading contamination worldwide, as much as the primary spreading contamination [11], [12]. …”
Section: Diffusion Of Radioactive Substancementioning
confidence: 99%
“…Numerical simulation showed that the radionuclides derived from FNPP1 circulated around the Northern Hemisphere (Stohl et al, 2012), and the fission products were actually detected in aerosol, gaseous, rain and snow samples collected in North America (e.g., Bowyer et al, 2011;Leon et al, 2011), Europe (e.g., Bossew et al, 2012;Masson et al, 2011), central Russia (Bolsunovsky & Dementyev, 2011;Melgunov et al, 2012) and Taiwan (Huh et al, 2012). The radionuclides emitted from FNPP1 were also detected from terrestrial biota not only in Japan (e.g., Hashimoto et al, 2012;Higaki et al, 2012;Tagami et al, 2012) but also in North America (Thakur et al, 2012) and Europe Pittauerova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%